1974
DOI: 10.1111/j.1469-7998.1974.tb04378.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical conditioning of the environment by the freshwater pulmonate snails (Biomphalaria glabrata) and its effect on growth and natality rates

Abstract: The effects of heterotypically conditioned media on the growth and natality rates of Biomphalaria glabrata have been studied under conditions which prevented the assay snails from being stimulated by tactile and visual signals from other snails. It was demonstrated that increasing the density of snails producing the conditioned medium up to a critical threshold resulted in enhancement of growth and natality rates. Further increases in density beyond the optimum level caused a reduction in growth and natality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The experimental method used has been described by Thomas, Goldsworthy & Benjamin (1974). Each assay snail was kept isolated in 200 ml of medium in 1 of 10 compartments of an inner tank made of white, opaque perspex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental method used has been described by Thomas, Goldsworthy & Benjamin (1974). Each assay snail was kept isolated in 200 ml of medium in 1 of 10 compartments of an inner tank made of white, opaque perspex.…”
Section: Methodsmentioning
confidence: 99%
“…Further increases in snail numbers or a decrease in volume or conditioning time can have the opposite effect. It has further been shown that these effects can be induced by chemical conditioning alone (Thomas, 1973 ;Thomas, Goldsworthy & Benjamin, 1974). The purpose of the investigations described in the present paper is to measure the effects of chemical environments produced by plant fed snails kept at densities of 10, 20, 30, 50, 90 and 170 snails per 6 1 on some of their growth characteristics and metabolism.…”
Section: Introductionmentioning
confidence: 96%
“…Vernon (1995) suggested that an absence of social facilitation, caused by deprivation of social communication as a result of isolation, may play a role in reducing reproductive output of isolated B. glabrata although the substance(s) that are responsible for this observation are not known. Basommatophoran freshwater snails may release communication substances in the water that may influence feeding, growth, metabolism and reproduction in conspecifics (Ritchie et al, 1966;Thomas et al, 1974Thomas et al, , 1975. Individuals of B. glabrata are thought to be receptive to even very low concentrations of chemicals that are released by nearby conspecifics but the exact nature of these communication substances is not yet known.…”
Section: Social Facilitationmentioning
confidence: 99%
“…Growth rates decline after egg laying and are inversely proportional to oviposition rates ( P. canaliculata ; Albrecht et al ., ). Apart from direct competition for limited food resources, lower growth rates under crowded conditions may also be due to chemical suppressants, including growth suppressive chemicals such as occur in slime trails of other aquatic snails (Berrie & Visser, ; Thomas et al ., , ). The possibility that suppressive chemicals may determine apple snail growth and development in paddy fields has received little research attention.…”
Section: Density Dependence and Intraspecific Competitionmentioning
confidence: 99%